2022
DOI: 10.1001/jamanetworkopen.2022.16784
|View full text |Cite
|
Sign up to set email alerts
|

Australian Women’s Intentions and Psychological Outcomes Related to Breast Density Notification and Information

Abstract: Key Points Question What is the effect of mammographic breast density notification and information provision on women’s intention to seek supplemental screening and self-reported psychological outcomes? Findings In this randomized clinical trial of 1420 women living in Australian jurisdictions without widespread breast density notification, women who viewed a hypothetical screening mammogram results letter with breast density notification and information we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…This was mainly driven by the psychological impact of the possibility or increased risk of cancer. In previous studies, it has been shown that providing breast density notification and accompanying information can improve knowledge about the reduced sensitivity of mammography in dense breasts and the increased risk of breast cancer; however, this may also increase women’s anxiety and confusion [ 13 , 21 ]. In order to mitigate any unintended outcomes, such as anxiety, the phrasing of the BD notifications should be carefully crafted to enhance the understanding of the notifications so that the women are accurately informed [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was mainly driven by the psychological impact of the possibility or increased risk of cancer. In previous studies, it has been shown that providing breast density notification and accompanying information can improve knowledge about the reduced sensitivity of mammography in dense breasts and the increased risk of breast cancer; however, this may also increase women’s anxiety and confusion [ 13 , 21 ]. In order to mitigate any unintended outcomes, such as anxiety, the phrasing of the BD notifications should be carefully crafted to enhance the understanding of the notifications so that the women are accurately informed [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our earlier qualitative studies 22 , 23 and experimental RCT 24 — co‐designed with input from BreastScreen collaborators, as well as local and state community and BreastScreen Queensland panels that included Aboriginal and Torres Strait Islander women — informed the RCT study design and the additional information provided.…”
Section: Methodsmentioning
confidence: 99%
“…Full methods of the trial are reported elsewhere. 11 Data were analysed using generalised linear regression models with a modified Poisson approach (Poisson distribution with a log-link and robust standard errors) to permit estimation of adjusted relative risks and corresponding 95% confidence intervals for intention to seek supplemental screening (ultrasound or MRI), relative to all other screening intention options. Given the exploratory nature of the analysis, potential covariates were first included in a simple adjustment model, including the covariate and the randomised condition (adapted letter from WA and HL sensitive letter).…”
Section: Methodsmentioning
confidence: 99%